Plasmonic dye-sensitized solar cells using core-shell metal-insulator nanoparticles. - Brown, MD; Suteewong, T; Kumar, R; D'Innocenzo, V; Petrozza, A; Lee, M; Wiesner, U; Snaith, H (2011)
We present an investigation into incorporating core-shell Au-SiO(2) nanoparticles into dye-sensitized solar cells. We demonstrate plasmon-enhanced light absorption, photocurrent, and efficiency for both iodide/triiodide electrolyte based and solid-state dye-sensitized solar cells. Our spectroscopic investigation indicates that plasmon-enhanced photocarrier generation competes well with plasmons oscillation damping with in the first tens of femtoseconds following light absorption.